Elements of Cultures of other Races as National Identity and Unifying of Malaysians in Dewan Bahasa dan Pustaka's Selected poems: (Unsur Budaya Kaum Lain sebagai Jati Diri Kebangsaan dan Pemersatu Bangsa Malaysia dalam Sajak Pilihan Terbitan Dewan Bahasa dan Pustaka) (Malay Literature, 2019)
National identity is the core of nation building, especially for a nation that is made up of different races and cultural backgrounds, as is Malaysia. It is imperative for the country, therefore, that there is understanding and appreciation on the part of society of a national identity. The purpose of this research is to analyse national identity in the poems under study, and subsequently to preserve the national identity in these poems published by Dewan Bahasa dan Pustaka. The method used in this study of selected poems published by DBP from 2010 until 2015 was close reading and content analysis. The study's analysis employed the principles of the National Culture Policy 1971 as its conceptual framework by focusing on the aspect of other cultures' elements as a part of national identity. The results of the study show that the poems analysed recognize that cultures of other races are freely practiced, while the elements of other ethnic cultures that fit with the principles of the National Culture policy become a unifying element of the people and the catalyst of the national identity of Malaysia.Keywords: National identity; nation, National Culture Policy, Dewan Bahasa dan Pustaka